Respostas
respondido por:
3
4x² - 27 = x²
4x² - x² - 27 = 0
3x² - 27 = 0
3x² = 27
x² = 27/3
x² = 9
x =![\displaystyle \mathsf{\sqrt{9}} \displaystyle \mathsf{\sqrt{9}}](https://tex.z-dn.net/?f=%5Cdisplaystyle+%5Cmathsf%7B%5Csqrt%7B9%7D%7D)
x =![\displaystyle \mathsf{\pm \sqrt{9}} \displaystyle \mathsf{\pm \sqrt{9}}](https://tex.z-dn.net/?f=%5Cdisplaystyle+%5Cmathsf%7B%5Cpm+%5Csqrt%7B9%7D%7D)
Resposta:![\displaystyle \mathsf{\pm \sqrt{9}} \displaystyle \mathsf{\pm \sqrt{9}}](https://tex.z-dn.net/?f=%5Cdisplaystyle+%5Cmathsf%7B%5Cpm+%5Csqrt%7B9%7D%7D)
4x² - x² - 27 = 0
3x² - 27 = 0
3x² = 27
x² = 27/3
x² = 9
x =
x =
Resposta:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás